Final adult height in children with central precocious puberty – a retrospective study - Knific, Taja; Lazarevič, Melisa; Žibert, Janez; Obolnar, Nika; Aleksovska, Nataša; Šuput Omladič, Jasna; Battelino, Tadej; Avbelj Stefanija, Magdalena (Frontiers in Endocrinology, 2022)
Background/Aims: Central precocious puberty (CPP) is due to premature activation of the hypothalamic-pituitary-gonadal axis. It predominantly affects girls. CPP leads to lower final height (FH), yet the treatment benefit in girls between 6 and 8 years is equivocal. Our main goal was to evaluate the effects of gonadotropin-releasing hormone analogue (GnRHa) on FH and identify factors that predict FH. Methods: In a retrospective study, children with CPP (12 boys, 81 girls) that reached FH were included. Their clinical data at diagnosis and up to their final height was compared by descriptive statistics among idiopathic (iCPP) (n=68) and non-idiopathic CPP (nCPP) and between GnRHa treated (n=48) and untreated (n=15) girls with iCPP. The treatment effect of body weight (BW) adjusted GnRHa dosing was evaluated. Univariate linear regression and step-wise multivariable regression including 48 girls with iCPP treated with GnRHa were performed to identify predicting factors for FH. Results: Children with idiopathic CPP (iCPP) reached higher FH (p=0.002) than children with non-idiopathic CPP. After the diagnosis, the treated group gained 7.0 cm more than the untreated group. Yet, attributable to individualized decision-making, the FH in both groups was comparable (161.5 cm in treated, 161.0 cm in untreated girls with iCPP), although the onset of menarche was 2.5 years earlier among untreated girls. BW-adjusted dosing suppressed peak luteinizing hormone (LH) below 4.5 IU/L in 95% of children; however, bone age further advanced during therapy in 38% of patients. Predicting factors revealed by multivariable regression were bone age at diagnosis, BMI SDS at diagnosis, LH basal, age at start and cessation of treatment, predicted adult height and target height. (R2=0.72). Conclusion: Children with nCPP had worse FH outcome compared to iCPP despite similar CPP onset and therapeutic characteristics. Treatment by GnRHa using BW-adjusted dosing was effective in delaying menarche onset and reaching target height in girls with iCPP. Multiple factors affecting FH outcome indicated individualized decision-making regarding therapeutic intervention remains challenging. In the treated patients, among the factors that can be influenced, height at treatment cessation most significantly influenced the final outcome.